On “Local Theory” Neutrality with Respect to “Meta-Theories” and Data from a Diversity of “Native Speakers”, Including Heritage Speaker Bilinguals: Commentary on Hulstijn (2024) - Jason Rothman; Fatih Bayram; Jiuzhou Hao; Patrick Rebuschat (Languages)
This commentary critically engages with Hulstijn’s revised Basic Language Cognition (BLC) Theory, which aims to enhance explanatory power and falsifiability regarding individual differences (IDs) in language proficiency across native and non-native speakers. While commending BLC Theory’s emphasis on separating oral and written language cognition, we raise two key concerns. First, we question the theory’s exclusive alignment with usage-based approaches, arguing that its core constructs are, in principle, compatible with multiple meta-theoretical frameworks, including generative ones. As such, BLC Theory should remain neutral to maximize its cross-paradigmatic utility. Second, we address the theory’s treatment of heritage speaker bilinguals (HSs), particularly the implication that they may not typically acquire BLC. We contend that this position overlooks robust empirical evidence demonstrating that HSs develop systematic, rule-governed grammars influenced by their individual input and usage conditions. Moreover, we highlight how IDs among HSs can provide a valuable testing ground for BLC Theory, particularly regarding the role of input and literacy. We conclude that embracing theory neutrality and integrating diverse speaker data—especially from heritage bilinguals—can enhance BLC Theory’s generalizability, empirical relevance, and theoretical utility across language acquisition research.